CTA - ten years of service to ACP countries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The first ten years: Technical Centre for agriculture and rural cooperation (ACP-EEC) CTA